Nurses' knowledge regarding recommended practices on using surgical attire in operating theatre - Joshua Alayemi; Wilma ten Ham-Baloyi; Sihaam Jardien-Baboo (AOSIS, 2024)
Background: To reduce the risk for surgical site infections, nurses in the operating theatre environment must have knowledge of and adhere to recommended practices regarding the use of surgical attire. Aim: To evaluate the effect of an educational intervention on nurses' knowledge related to recommended practices regarding the use of surgical attire in operating theatre. Setting: Operating theatres in two public and two private hospitals in the Eastern Cape province, South Africa. Methods: An educational pilot study, using a quasi-experimental, two-group pre- and post-test design, was conducted. A convenience sample of n = 85 nurses was purposively allocated to a control group and an intervention group. An existing educational intervention consisting of an interactive training session, brochures based on the Association of periOperative Registered Nurses' (AORN) guidelines and a summary of these guidelines was implemented for the intervention group, while the control group received only the summary of the guidelines. Data were collected through self-administered pre- and post-test questionnaires from March 2019 to August 2019. Results: The overall knowledge score for nurses in the intervention group post-intervention improved with a large significance (p ≤ 0.000 and Cohen's d = 1.26). Conclusion: The intervention has shown potential to improve the knowledge related to recommended practices of nurses in operating theatres regarding the use of surgical attire. Contribution: This pilot study encourages the implementation of the intervention on the use of surgical attire but requires further development and a wider implementation to measure its impact, and access to resources, enhancing and sustaining its success.